Performance evaluation of PAPR in OFDM system using median codeword shift and hybrid median codeword shift method / Mohd Danial Rozaini …[et al.] - Rozaini, Mohd Danial; Idris, Azlina; Mohd Ali, Darmawaty; Abdullah, Ezmin (Universiti Teknologi MARA, 2019)
Orthogonal Frequency Division Multiplexing (OFDM) is the solutions to the current demand for a system having high data rate, capable to improve spectral efficiency and have the immunity against frequency selective fading. However, high peak to average power ratio (PAPR) is the major issue faced by every multicarrier modulation technique including OFDM systems. This paper presents a Median Codeword Shift (MCS) method, which is based on Selective Codeword Shift (SCS) scheme, to overcomes the PAPR problem in OFDM system. The manipulation of codeword structure and permutation process is the key to achieve better PAPR reduction in MCS method. In addition, the hybrid version of MCS is also being proposed by combining MCS with companding technique to further improve the PAPR performance. The simulation results show that MCS overcomes conventional OFDM and SCS with 24% improvement and 0.5 dB difference from SCS. The hybrid MCS also managed to achieve outstanding result with average of 74.4% improvement with tolerable degradation in BER performance.